How the National Flood Insurance Program (NFIP) Works - Carol Fountain; Michael T. Olexa; Jana Caracciolo; Lauren Grant (EDIS)
This 3-page fact sheet is a minor revision written by Michael T. Olexa, Jana Caracciolo, and Lauren Grant, and published by the Food and Resource Economics Department, October 2019.